First assessment on the microstructure and mechanical properties of gtaw-gmaw hybrid welding of 6061-t6 AA. (November 2020) - Rodríguez-Hernández, T.; Cruz-Hernández, V.L.; García-Rentería, M.A.; Torres-Gonzalez, R.; García-Villarreal, S.; Curiel-López, F.F.; Falcón-Franco, L.A.
Graphical abstract: Highlights: Hybridization of GTA and GMA welding of 6061-T6 AA hindered the growth of Mg2Si precipitates in the HAZ. Welds made with Hybrid GTAW-GMAW presented better mechanical properties in the as weld and after artificial aging condition. Welds made with GTAW-GMAW hybrid process reduces the porosity in weld metal. The electric arc interaction of the GTAW-GMAW hybrid process promote the grain structure refinement in weld metal. Abstract: Plates of 6061-T6 aluminum alloy of 6.35 mm thick were welded by using the hybrid gas tungsten arc - gas metal arc welding process (GTAW-GMAW) and compare with the conventional gas metal arc welding (GMAW). An ER-5356 filler wire of 1.2 mm in diameter and argon of high purity as protective gas were used in both processes. The aim of the experiments was to assess the effects that yield the GTAW-GMAW welding process on the microstructure and the mechanical properties of the welded joints in the as weld and after artificial aging condition. Heat inputs were set up between ∼ 0.9 kJ/mm and ∼ 1.1 kJ/mm. Plots of the grain size and porosity ratio showed that GTAW-GMAW promoted a grain structure refinement and a reduction of porosity in weld metal. In addition, GTAW-GMAW indicate a reduction on the degradation in the heat affected zone in the as weld condition and a 40 % increase in welding speed. There was observed a major losing of magnesium in weld metal in the conventional GMAW process, this effect reflects on the final mechanical strength and microhardness of weld metal after artificial aging, as less Mg is available to get in solid solution.